Psychological Balance Scale: Validation Studies of an Integrative Measure of Well-Being - Besika, Anastasia; Horn, Andrea B.; Martin, Mike (Frontiers in Psychology, 2021)
Studies infer Psychological Balance from the absence of psychopathology. In this article, we investigated this construct as an antecedent of well-being. We present empirical evidence toward the validation of a new theoretical model regarding Psychological Balance, a dynamic state with relatively constant characteristics, comprising Consistency and Flexibility and influenced by a Self/Others Ratio. A battery of 31 items, as indicators of Consistency, Flexibility and Self/Others Ratio, aided this empirical investigation. In an online study (N = 933) we collected cross-sectional data from the United Kingdom. Results of cross-validation analyses provided evidence toward the validity of the proposed model and the psychometric properties of its instrument. There were statistically significant associations between Consistency (i.e., degree of integration of a universal value structure as self-related characteristics that motivate personal goals and behavior), Flexibility (i.e., degree of ability to re-define meaningful and important goals in response to situational challenge) and five well-being variables (e.g., Meaning in Life). Self/Others Ratio (i.e., ratio of motivation to serve self-interest and the interest of others), operationalized as a binary variable (e.g., close and away from 1), moderated some of these associations. Altogether, this work may contribute toward a nuanced understanding of well-being and form the basis of interventions that aim to decrease emotional discomfort and increase meaning, happiness and life satisfaction.